Хеппи-энд для Дездемоны - Донцова Дарья Аркадьевна (Иронический детектив, 2007)
Экземпляры: аб (20170719) / Инвентарный номер: 51111 / Цена: 70.00 / Сис.шифр: Р2 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6